ANALISIS PERAN PEMERINTAH DALAM PENGENDALIAN TINGKAT PENGANGGURAN TERBUKA DI JAWA TIMUR PASCA COVID-19 - Alkhatiri, Zein Syakhur; Santoso, Dwi Budi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The post-COVID-19 open unemployment rate (TPT) tends to rise sharply. In this case, the role of the government needs to be focused on The government's role can be reflected through three main mechanisms to keep the open unemployment rate down mechanisms in keeping the TPT down, namely setting the minimum wage, stimulating economic growth, and population control. economic growth, and population control. This study aims to determine the impact of the government's role in controlling the open unemployment rate in East Java. open unemployment in East Java. This study uses secondary data in the form of panel data, with a time span of 2017-2022 and covering 38 districts/cities in East Java. districts/cities in East Java. The analysis method used is the panel data method. panel data method. The results show that the minimum wage contributes to increase in unemployment, economic growth can reduce unemployment, while population control also reduces unemployment rate. Therefore, the government needs to consider the positive and negative impacts of the three instruments to achieve an optimal effect.